1985
DOI: 10.1007/bf00139438
|View full text |Cite
|
Sign up to set email alerts
|

Scales of climate impacts

Abstract: Climates, ecosystems, and societies interact over a tremendous range of temporal and spatial scales. Scholarly work on climate impacts has tended to emphasize ~fferent questions, variables, and modes of explanation depending on the primary scale of interest. Much of the current debate on cause and effect, vulnerability, marginality, and the like stems from uncritical or unconscious efforts to transfer experience, eonciusions, and insights across scales. This paper sketches a perspective from which the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(82 citation statements)
references
References 29 publications
(18 reference statements)
2
79
0
1
Order By: Relevance
“…Global climate change, and changes in the concentrations of greenhouse gases, will have major effects on the vegetational patterns at local and regional scales (MacArthur 1972, Clark 1985; in turn, changes that occur at very fine scales, such as alterations in rates of stomatal opening and closing, ultimately will have impacts at much broader scales (Jarvis and McNaughton 1986). General circulation models (GCMs), which form the basis of climate prediction, operate on scales of hundreds of kilometres on a side, treating as homogeneous all of the ecological detail within (Hansen et al 1987, Schneider 1989).…”
Section: Global Climate Change and Ecological Modelsmentioning
confidence: 99%
“…Global climate change, and changes in the concentrations of greenhouse gases, will have major effects on the vegetational patterns at local and regional scales (MacArthur 1972, Clark 1985; in turn, changes that occur at very fine scales, such as alterations in rates of stomatal opening and closing, ultimately will have impacts at much broader scales (Jarvis and McNaughton 1986). General circulation models (GCMs), which form the basis of climate prediction, operate on scales of hundreds of kilometres on a side, treating as homogeneous all of the ecological detail within (Hansen et al 1987, Schneider 1989).…”
Section: Global Climate Change and Ecological Modelsmentioning
confidence: 99%
“…E a r l i e r i n t h e growing season p r e c i p i t a t i o n i s n o t a s important a p r e d i c t o r because s t o r e d s o i l -w a t e r i s g e n e r a l l y a v a i l a b l e and t h e p l a n t ' s water demand i s not a s g r e a t . Ratios of corn yield (Kalamazoo: Lenawee counties) vs. precipitation for the periods of a) April-May, b) May-June, c) JuneJuly, and d) July-August, 1945-1985 That our correlations are not stronger could be due to a number of factors. First, precipitation data are from a single county station while yield estimates are from the entire county.…”
Section: County To Remove D I F F E R E N C E S Due T O T O T a L Anmentioning
confidence: 67%
“…Seasonal dmamics of abovegoumd p h a~s~~e t i @ a l l y -a c t i v e biomass @an be infemed &am sabllib-based absemations, such as the normalized-&Eerence vegehtion index (NDVT) (&ward et d, 1985, Justice et al, 1985. showed that i n b r a n n d variabifity in the of a combination of spriw temperatures and n events results in marked year-to-year variation in estabEshent of blue grama with long-tern consequences stnrctwe (Coffin and Lauemoth 1990).…”
Section: Ual Precipitationmentioning
confidence: 99%
“…The literature reports an increasingly urgent need for developing interdisciplinary approaches (FERREIRA, 2000;2004;BRAGA et al, 2006;EVANS et al, 2009;MORAN, 2009;BUARQUE et al, 2014), which consider multiscale analysis to understand and offer methods to integrate, analyze and monitor the changing processes in ecological and social systems (CLARK, 1985;TURNER II et al, 1990;ROTMANS and ROTHMAN, 2003;MEA, 2003;VANWEY et al, 2009;MORAN, 2011) and to incorporate appropriate concepts and methods to understand and measure the vulnerability and adaptability of populations facing situations caused by climate change (ALVES, 2009;MORAN, 2009;MARANDOLA Jr. and D'ANTONA, 2014).…”
Section: Integrating Multiple Scales: Interdisciplinarity In the Vulnmentioning
confidence: 99%